Still Digging: Advances and Perspectives in the Study of the Diversity of Several Sedentarian Annelid Families - Maël Grosse (Diversity, 2021)
Sedentarian annelids are a diverse and heterogeneous group of marine worms representing more than 8600 species gathered in ca. 43 families. The attention brought to these organisms is unevenly distributed among these families, and the knowledge about them sometimes scarce. We review here the current knowledge about the families Acrocirridae, Cirratulidae (including Ctenodrilidae), Cossuridae, Longosomatidae, Paraonidae, and Sternaspidae in terms of biodiversity as well as the evolution of the taxonomy and systematics of each group. We present the challenges faced when studying these organisms and compare methodologies across groups and perspectives in future research.